The Depiction of Slavery through Animal Treatment in Sewell’s Black Beauty in Relation to Living with Environment - Sri Wahyuni; Sudarmin Harun (Hasanuddin University, 2018)
The purposes of this research were (1) to elaborate the kind of slavery depiction through animal treatment in Sewell’s Black Beauty and (2) to exposure how the human treatment to horses in the novel is considered as a form of slavery in England Victorian age. The data were obtained from Sewell’s Black Beauty through a descriptive qualitative method by applying Sociological Approach. The study concluded that human treatment to horses is considered slavery for violating laws on animal protection. Horses are created to work but also there are rules in using them. There were four animal Anti-Cruelty laws in 1867 existed in the novel. Those laws are penalty for overdriving cruelly treating animal, for impounding animals without giving sufficient food and water, penalty for carrying animals in a cruel manner and penalty for abandoning infirm animals in public place. This study also suggest human being that there is no rights of one creature to judge another creatures.